Pemberdayaan Ibu Rumah Tangga melalui Pelatihan Decoupage Pot Tanaman sebagai Upaya Pengembangan Ekonomi Kreatif di Kelurahan Kemang Manis - Kurnia Saputri; Sherly Marliasari; Sri Yuliani; M. Daffa Ghazan Alfaeza; Eka Apriani (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Limited access to productive skills training remains a major constraint in the development of household-based creative economies, particularly among housewives in Kemang Manis Village. This community service program aimed to enhance community skills and creativity through training in decorating plant pots using the decoupage technique, which has aesthetic and economic value. The activity was implemented through several stages, including preparation, hands-on practical training, evaluation of participants’ work, and mentoring for the establishment of small business groups. A total of 30 participants took part in the program using a participatory approach. The results indicate that participants were able to understand and apply basic decoupage techniques to plant pots and produce handicraft products with potential market value. In addition to improving individual skills, the program encouraged the formation of small business groups to support the sustainability of productive community activities. Overall, this community service program contributed to strengthening economic independence and community empowerment through creative skill development.